Filsafat Ilmu Pendidikan Islam dalam Perspektif Pendidikan Jasmani - Budiman, Sri (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2021)
Islamic education is a science that teaches people to be better. Humans also need a healthy body to survive. Therefore, it is necessary to study the material on the philosophy of Islamic education in the perspective of physical education. Human beings need knowledge to be able to solve every problem in life. Science that is very closely related to life is the science of Islamic education. Islamic education teaches life in accordance with Islamic values. Leaders in life must have strong physical and health mental to be able the overcome various problems. Efforts in improving physical health can be made by studying physical education. Muslims have long since applied physical education in learning and defending Islam. The religious foundation in physical education based on the Quran and hadith proves that Islamic religious education is interconnected with physical education and complements each other in supporting human life as caliphs on earth.